2016
DOI: 10.1016/j.jaad.2016.01.050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical diclofenac 3% and calcitriol 3 μg/g on superficial basal cell carcinoma (sBCC) and nodular basal cell carcinoma (nBCC): A phase II, randomized controlled trial

Abstract: Mosterd, K. (2016). The effect of topical diclofenac 3% and calcitriol 3 g/g on superficial basal cell carcinoma (sBCC) and nodular basal cell carcinoma (nBCC): A phase II, randomized controlled trial. Journal of the American Academy of Dermatology, 75(1), 126-134. https://doi.org/10.1016/j.jaad.2016.01.050 General rightsCopyright and moral rights for the publications made accessible in Discovery Research Portal are retained by the authors and/or other copyright owners and it is a condition of accessing public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
0
28
1
2
Order By: Relevance
“…Combination therapy showed a significant decrease in Ki-67, and complete histologic tumor regression was seen in 43.8% of those with sBCC. However, there were no significant changes in patients with nBCC [61] .…”
Section: Smo Inhibitorsmentioning
confidence: 73%
“…Combination therapy showed a significant decrease in Ki-67, and complete histologic tumor regression was seen in 43.8% of those with sBCC. However, there were no significant changes in patients with nBCC [61] .…”
Section: Smo Inhibitorsmentioning
confidence: 73%
“…Clinical trials have shown that celecoxib may be effective for the prevention of NMSC, including BCCs, in high‐risk skin cancer patients . Result of a recent phase II clinical trial demonstrated that topical diclofenac therapy promotes tumor regression of superficial BCCs and alleviates anti‐apoptotic and proliferative markers …”
Section: Interventionsmentioning
confidence: 99%
“…175 Result of a recent phase II clinical trial demonstrated that topical diclofenac therapy promotes tumor regression of superficial BCCs and alleviates anti-apoptotic and proliferative markers. 176…”
Section: Immunotherapymentioning
confidence: 99%
“…Other studies, using variable concentrations, excipients, or other combinations of considered drugs may be profitable in the optimization of new treatments. Thus, although surgical excision is still the best option for all BCC, topical gel diclofenac constitutes an auspicious noninvasive new approach for low-risk superficial BCC [89]. Like diclofenac, piroxicam has been shown to exert antitumorigenic effects.…”
Section: Classical Therapy Of Nmscsmentioning
confidence: 99%